Research At Universiti Sains Malaysia Volume 1 Policy Studies And Consultancy Services - K.J. Ratnam, K.J. Ratnam; Muhamad Jantan, Muhamad Jantan; Saravanamuttu, Johan; Wan Muda, Wan Abdul Manan (Universiti Sains Malaysia, 2004)
This volume is one of four published in conjunction with University Sains Malaysia's thirty-fifth anniversary (the other three being devoted to Biotechnology, Environmental Management and Engineering and The Natural Habitat) and its primary focus is on policy and developmental issues and on the University's contribution to the outside community through consultancy and other services. This would cover research work carried out in Schools such as the School of Social Sciences, the School of Humanities, the School of Education and the School of Management, while not neglecting research centres such as the Centre for Policy Research, the Women's Development Research Centre, the Centre for Drug Research and others. The selection of works presented in this volume which is by no means exhaustive, is representative of USM's contributions on policy and related matters during its thirty-five year history.